2009
DOI: 10.1007/s11224-009-9527-8
|View full text |Cite
|
Sign up to set email alerts
|

Coordination behaviour of 2,2′-bipyridine towards the dichloroacetates of zinc and cadmium

Abstract: The coordiantion compounds [Zn(C 10 H 8 N 2 ) (Cl 2 HCCOO)(H 2 O) 3 ] -Á[Zn(C 10 H 8 N 2 )(Cl 2 HCCOO) 3 ] ? and [Cd(C 10 H 8 N 2 ) 2 (Cl 2 CHCOO) 2 ] were synthesised and characterised by elemental and thermal analysis, IR and UV-VIS spectroscopy, and X-ray crystallography. The complexes are air stable and well-soluble in water. The zinc atoms are five and six coordinated and the cadmium atom is six coordinated. The coordination polyhedra of central atoms can be described as trapezoidal pyramid and octahedron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The value of R Zn-S redetermined for coordination compounds, as was described previously (Trzesowska et al, 2004(Trzesowska et al, , 2005(Trzesowska et al, , 2006, was 2.092 Å . The values R Zn-O = 1.6950 Å and R Zn-N = 1.7588 Å were taken from literature data (Kruszynski, 2010). The computed bond valences showed that in (I) the strongest coordination bond is the Zn1-N6 bond ( ZnN = 0.609 v.u.…”
Section: Resultsmentioning
confidence: 99%
“…The value of R Zn-S redetermined for coordination compounds, as was described previously (Trzesowska et al, 2004(Trzesowska et al, , 2005(Trzesowska et al, , 2006, was 2.092 Å . The values R Zn-O = 1.6950 Å and R Zn-N = 1.7588 Å were taken from literature data (Kruszynski, 2010). The computed bond valences showed that in (I) the strongest coordination bond is the Zn1-N6 bond ( ZnN = 0.609 v.u.…”
Section: Resultsmentioning
confidence: 99%
“…In lithium compounds the hmta molecules are located in the outer coordination sphere and in sodium, potassium and rubidium compounds in the inner coordination sphere. The thermal decomposition of studied compounds proceeds via halogenides or metal oxides with evolving halogens [62][63][64] (Fig. 9).…”
Section: Resultsmentioning
confidence: 99%
“…The coordination interaction between organic ligands and metal ions with much higher bond energy (Scheme 1) is generally used in metal-organic frameworks, however, it has rarely been explored in hybrid perovskites. [25][26][27] The heterocyclic aromatic ligands of bipyridine (Bpy, such as 4,4Bpy and 2,2Bpy) are hydrophobic and electron-conjugated heterocyclic aromatic ligands, featuring two N atoms with a lone pair of electrons, and have been extensively utilized in the areas of coordination chemistry and serve as an ideal platform to design intrinsic water-stable organo-lead halide crystalline materials by constructing Pb-N coordination structures. 28 Also, owing to the presence of an empty p orbital in Bpy, the corresponding Pb-N coordination structures may possess chargetransfer features in the visible spectrum, which endow the targets with good photoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%